1988
DOI: 10.1002/mpo.2950160206
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐needle aspiration biopsy in children: Experience in 70 cases

Abstract: Results of 70 fine-needle aspiration biopsies (FNAB) were evaluated retrospectively in 61 pediatric patients. Over a period of 9 months all mass lesions suspected being malignant were aspirated. Twelve of the 70 aspirations were performed in children having known tumours, in order to exclude recurrence or metastasis. The others were carried out to obtain a diagnosis. Satisfactory specimens were obtained from 58 (83%). There were 21 benign diagnoses, 36 malignant diagnoses, and 1 with suspected malignancy. Corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…When required, both FNA and CNB techniques provide adequate samples. The cellularity was judged satisfactory in 82% to 85% of our cases, in agreement with the literature (i.e., 76% to 93% for FNA and 80% to 95% for CNB) . However, our data confirm a significantly higher diagnostic accuracy of CNB, as previously reported .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…When required, both FNA and CNB techniques provide adequate samples. The cellularity was judged satisfactory in 82% to 85% of our cases, in agreement with the literature (i.e., 76% to 93% for FNA and 80% to 95% for CNB) . However, our data confirm a significantly higher diagnostic accuracy of CNB, as previously reported .…”
Section: Discussionsupporting
confidence: 92%
“…The cellularity was judged satisfactory in 82% to 85% of our cases, in agreement with the literature (i.e., 76% to 93% for FNA and 80% to 95% for CNB). [13][14][15]17,[45][46][47][48][49][50][51] However, our data confirm a significantly higher diagnostic accuracy of CNB, as previously reported. 13,[15][16][17][18]52,53 Nevertheless, in our experience, FNA remains useful in several settings: it allows extemporaneous examinations during the procedure, helping physicians performing biopsies to adjust the amount of tissue to be obtained.…”
Section: However the Relevant Tumor Volume Threshold Below Which A Bsupporting
confidence: 92%
“…FNAC for histological confi rmation prior to chemotherapy was allowed in the 2001-SIOP Wilms tumor protocol, with no risk of upstaging [14]. Different studies have been reported regarding the effectiveness of FNAC in the diagnosis of renal tumors in children [15][16][17]. However, some investigators consider FNAC as a sub-optimal diagnostic tool, with a high rate of false positives and negatives [18].…”
Section: Discussionmentioning
confidence: 97%
“…For these reasons, in the UKCCSG WT Study 3 pre-chemotherapy histologic diagnosis obtained by biopsy was required. Although some advocate percutaneous FNA as a reliable means of recognising histologic features of renal tumors of childhood [10], other studies have shown to be a suboptimal method with both false-positive and false-negative results [11].…”
Section: Discussionmentioning
confidence: 99%